Do carbonate precipitates affect dissolution?: 1: Basaltic glass - Stockmann, G.; Wolff-Boenisch, Domenik; Gislason, S.; Oelkers, E. (Elsevier Science BV, 2011)
Basaltic glass dissolution rates were measured in mixed-flow reactors at basic pH and at 25 °C and 70 °C in aqueous solutions supersaturated with respect to calcite for up to 140 days. Inlet solutions were comprised of NaHCO3±CaCl2 with ionic strengths N0.03 mol kg−1. Scanning Electron Microscope images show that significant CaCO3 precipitated during these experiments. This precipitate grew on the basaltic glass in experiments performed in Ca-free inlet solutions, but nucleated and grew independently of the glass surfaces in experiments performed in Ca-bearing inlet solutions. In those experiments where CaCO3 precipitated on the glass surface, it grew as discrete crystals; no pervasive CaCO3 layers were observed. The lack of structural match between glass and calcium carbonate favors CaCO3 nucleation and growth as discrete crystals. Measured basaltic glass dissolution rates based on either Si, Al, or Mg were both 1) independent of time during the experiments, and 2) equal to that of corresponding control experiments performed in NaHCO3-free inlet solutions. Taken together, these observations show that basaltic glass dissolution rates are unaffected by the precipitation of secondary CaCO3 precipitation. It seems therefore likely that carbonate precipitation will not slow basaltic glass dissolution during mineral sequestration efforts in basaltic rocks.